2022
DOI: 10.1055/a-1937-9692
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of Thromboembolic Events and Mortality Among Hospitalized Coronavirus 2019 Patients: Large Observational Cohort Study of Electronic Health Records

Abstract: Background: Most symptoms of COVID-19 are mild; however, some patients experience cardiovascular complications, including thromboembolic events and death. Data are needed to better inform prevention and treatment of these events. This analysis was designed to describe patient characteristics, medication use, thromboembolic events, and all-cause mortality in hospitalized COVID-19 patients in the United States. Methods: This retrospective, observational cohort study identified adults hospitalized with COVID-19 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 51 publications
0
10
0
1
Order By: Relevance
“…18 Early prospective data from the US placed the ATE rate at 1.71% in the 3-month post-discharge period, while a recently published retrospective observational study of 40,524 hospitalized patients with COVID-19 reported post-discharge rates of ischemic stroke, myocardial infarction, and acute limb ischemia of 1.18%, 1.53%, and 0.10%, respectively, at a mean follow-up of 70.7 days. 16,19 Further, in a recent meta-analysis of 7,816 discharged patients with COVID-19, ATE This article is protected by copyright. All rights reserved.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 3 more Smart Citations
“…18 Early prospective data from the US placed the ATE rate at 1.71% in the 3-month post-discharge period, while a recently published retrospective observational study of 40,524 hospitalized patients with COVID-19 reported post-discharge rates of ischemic stroke, myocardial infarction, and acute limb ischemia of 1.18%, 1.53%, and 0.10%, respectively, at a mean follow-up of 70.7 days. 16,19 Further, in a recent meta-analysis of 7,816 discharged patients with COVID-19, ATE This article is protected by copyright. All rights reserved.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…16 Subsequently, a recently published retrospective observational study of 40,524 hospitalized patients with COVID-19 reported post-discharge rates of ischemic stroke, myocardial infarction, and acute limb ischemia of 1.18%, 1.53%, and 0.10%, respectively at a mean follow-up of 70.7 days and time to first-event 71.6, 52.6, and 83.5 days, respectively. 19 Data from a recent meta-analysis of 7,816 discharged patients with COVID-19 showed an ATE rate of 1.46% for a post-discharge follow-up period of up to 6 months among the included studies, while another large metaanalysis of 20,875,843 patients in the post-acute phase of COVID-19 showed a cumulative postdischarge rate of incident MI between 0.1 to 1.1% with a mean follow-up of 8.5 months. 20,30 Lastly, the REMAP-CAP trial in hospitalized severe COVID-19 patients showed a benefit on 90day mortality, at the cost of a significantly increased risk of major bleeding in patients receiving antiplatelets (OR = 2.97; 95% CI, 1.23-8.28).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 2 more Smart Citations
“…Another nice example of a visual summary from TH Open is the paper by Spyropoulos et al 18 These also facilitate our social media activities, which include interviews with authors of featured papers, for example, this one by Kim et al 19 https://twitter.com/TH_Journal/status/15572940705061 80608.…”
Section: New Developmentsmentioning
confidence: 99%